Cervico-isthmic compression suture: an effective method to manage PPH during caesarean-section for placenta previa - Kumari, Ruby; Raj, Akanksha; Vijaya; Dwivedi, Lata Shukla; Deepjyoti; Rani, Poonam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Obstetric hemorrhage is the leading cause of maternal mortality, placenta previa and placenta accreta spectrum (PAS) are major causes of it. Most of time these bleeding don’t respond to uterotonics drugs in placenta previa. In failed first-line management of PPH, cervico-isthmic compression sutures are effective to control PPH from lower uterine segment in placenta previa. The objectives of this study were to determine effectiveness of Cervico-isthmic compression suture in management of PPH during caesarean section for placenta previa the primary outcome was assessed by the need of blood transfusion, caesarean hysterectomy, ICU care, total hospital stay and incidence of maternal mortality and the secondary outcome was to describe the complications of the procedure in peri-operative periods. Methods: This retrospective study was carried out in the department of obstetrics and gynecology, ANMMCH, Gayajee, from April 2025 to March 2023. It included 36 patients of placenta previa in which cervico- isthmic compression suture was applied. Results: In the study group the mean age was 27±4.18 years. The gestational age at the time of delivery ranges from 32.3 to 37.4 weeks. Postpartum hemorrhage was adeptly managed with the compression sutures in 34 patients (94.45%), while in 2 patients (5.5%), caesarean hysterectomy was needed. Notably, 66.66% of patients (n=24/36) necessitated blood transfusions during peri-operative periods. There was no any recorded maternal mortality. Conclusions: Cervico-isthmic compression suture is a simple, quick and effective measure for intractable bleeding from placental bed or atonic lower uterine segment in cases of placenta previa.